Cost-effectiveness of percutaneous patent foramen ovale closure as secondary stroke prevention. (3rd July 2018) - Tirschwell, David L.; Turner, Mark; Thaler, David; Choulerton, James; Marks, David; Carroll, John; MacDonald, Lee; Smalling, Richard W.; Koullick, Maria; Gu, Ning Yan; Saver, Jeffrey L.
Abstract: Objective: Compared to medical therapy alone, percutaneous closure of patent foramen ovale (PFO) further reduces risk of recurrent ischemic strokes in carefully selected young to middle-aged patients with a recent cryptogenic ischemic stroke. The objective of this study was to evaluate the cost-effectiveness of this therapy in the context of the United Kingdom (UK) healthcare system. Methods: A Markov cohort model consisting of four health states (Stable after index stroke, Post-Minor Recurrent Stroke, Post-Moderate Recurrent Stroke, and Death) was developed to simulate the economic outcomes of device-based PFO closure compared to medical therapy. Recurrent stroke event rates were extracted from a randomized clinical trial (RESPECT) with a median of 5.9-year follow-up. Health utilities and costs were obtained from published sources. One-way and probabilistic sensitivity analyses (PSA) were performed to assess robustness. The model was discounted at 3.5% and reported in 2016 Pounds Sterling. Results: Compared with medical therapy alone and using a willingness-to-pay (WTP) threshold of £20, 000, PFO closure reached cost-effectiveness at 4.2 years. Cost-effectiveness ratios (ICERs) at 4, 10, and 20 years were ₤20, 951, ₤6, 887, and ₤2, 158, respectively. PFO closure was cost-effective for 89% of PSA iterations at year 10. Sensitivity analyses showed that the model was robust. Conclusions: Considering the UK healthcare system perspective, percutaneous PFO closure in cryptogenic ischemic stroke patients is a cost-effective stroke prevention strategy compared to medical therapy alone. Its cost-effectiveness was driven by substantial reduction in recurrent strokes and patients' improved health-related quality-of-life.